Effectiveness of Lower Limb Exercise in Chronic Heel Pain: A Critical Narrative Review of Stretching, Progressive Loading and Regional Strengthening - Aishwarya Gandhi; Taruna Kumawat (Asian Journal of Medicine and Health, 2026)
Chronic heel pain is among the most frequent musculoskeletal complaints presenting to primary care, podiatry and physiotherapy services, and a substantial minority of those affected remain symptomatic for years. Exercise directed at the lower limb is recommended almost universally, yet the term covers interventions that differ in target tissue, contraction type, load magnitude, dose and degree of supervision. Whether those differences matter for clinical outcome remains contested. This critical narrative review examines the effectiveness of the principal categories of lower limb exercise used for chronic heel pain: tissue-specific plantar fascia stretching, calf stretching, progressive and heavy-slow resistance training, isometric loading, intrinsic foot muscle training and proximally directed strengthening. Literature was identified through structured searching of open scholarly indexes, supplemented by backward and forward citation searching and targeted author searching. Appraisal concentrated on case definition, dose reporting, outcome selection, interpretation against minimal important differences and the behaviour of comparison groups. Several patterns emerge from the synthesis. Tissue-specific plantar fascia stretching shows the most consistent short-term advantage over generic calf stretching, although the advantage attenuates and is no longer detectable at two years. High-load resistance training produced a large advantage at three months in one trial that was not sustained and has not been independently replicated; subsequent trials of standing heel-raise loading show improvement in all arms without between-group separation, and only a small minority of participants reach an acceptable symptom state. Isometric loading did not produce immediate analgesia in plantar fasciopathy, which contrasts with observations in tendinopathy of the knee. Evidence for intrinsic foot and hip-directed exercise remains preliminary. The dominant methodological constraints are inconsistent eligibility criteria, undocumented achieved dose, follow-up that is short relative to the natural history of the disorder, and substantial improvement within comparison arms. Confidence that any specific exercise formulation outperforms another is therefore low. Confidence that structured loading combined with education represents a defensible, low-cost first-line strategy is comparatively higher.